COMBINED TREATMENT OF OPERABLE RECTAL CANCER WITH NEGATIVE PROGNOSIS FACTORS: A PROSPECTIVE STUDY - S. O. Kochkina; S. S. Gordeyev; K. S. Petrov; Z. Z. Mammedli (Сибирский онкологический журнал)
Introduction. Neoadjuvant chemotherapy (nact) is a potential alternative to chemoradiation therapy (crt) for rectal cancer and may allow early prevention of distant metastasis.Objective: to study the safety and efficacy of nact for patients with rectal cancer without damage to the mesorectal fascia.Material and methods. From 2016 to 2019, patients with cancer of the upper ampullar (сmrt2-t4an+m0, cmrt4an0m0), medium ampullar (cmrt3сn0m0, cmrt2n+m0) rectal regions were included in the pilot prospective study. All patients underwent nact according to the capox 4 scheme. Evaluation of the effect was carried out on the basis of mri of the small pelvis. In the case of regression or stabilization, surgery was performed, and in the case of progression, crt was followed by surgery. After surgery, all patients were scheduled for adjuvant chemotherapy for a total duration of 6 months. The primary endpoint was the rate of pathological complete response (mandard trg 1). Secondary endpoints included disease progression, toxicity (nci-ctc v. 5.0), postoperative complications (clavien-dindo), chemotherapy regimen, and long-term treatment outcomes.Results. 136 patients were included into the study. Of 130 (11 %) patients, who underwent only nact prior to surgery, 15 had pathological complete response. 99 patients (72.8 %) received a full course of chemotherapy for 6 months (nact + adjuvant pct). 6 (4.3 %) patients after neoadjuvant chemotherapy were treated with crt, 5 (3.67 %) of them due to local progression according to mri data, 1 (0.7 %) due to grade 3 toxicity during 1 course of pct and inability to continue chemotherapy treatment plan. Radiation therapy resulted in partial tumor regression in all patients. Systemic progression was not observed in any patient. Grade iii–iv toxicity was observed in 7 (5.1 %) patients, including bronchospasm (n=2, 1.4 %), thrombocytopenia (n=1, 0.7 %), neutropenia (n=1, 0.7 %), peripheral neuropathy (n=1, 0.7 %), cardiotoxicity (n=1, 0.7 %), diarrhea (n=1, 0.7 %). Grade v toxicity (acute myocardial infarction) was observed in 1 (0.7 %) patient. R0 resection was performed in all cases. Grade iiia postoperative complications occurred in 6 (4.4 %) patients, iiib complications in 5 (3.7 %) patients, and death due to sepsis after postoperative pneumonia in 1 (0.7 %) patient. The frequency of anastomotic leak was 3.6 % (n=5). The median follow-up was 31.4 months, the overall survival (os) and disease-free survival (dfs) rates were 94 % and 92.8 %.Conclusion. Neoadjuvant chemotherapy is a promising treatment option for rectal cancer patients with negative prognostic factors.